2011
DOI: 10.1007/s13277-011-0287-x
|View full text |Cite
|
Sign up to set email alerts
|

System review and metaanalysis of the relationships between five metabolic gene polymorphisms and colorectal adenoma risk

Abstract: The relationships between some metabolic (including EPHX1, GSTs and NQO1) gene polymorphisms and colorectal adenoma (CRA) risk have been commonly studied, and no conclusions are available up to now. Therefore, we quantitatively studied the relationships by a metaanalysis. The databases of Medline and Embase were retrieved updated to June 15th, 2011. Crude or adjusted odds ratio (crude OR or adjusted OR) and 95% confidence interval (95%CI) were calculated to present the strength of the associations. Overall, ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…These include meta-analyses that suggest GSTM1 deficiency increases the risk of head and neck cancer (Hashibe et al, 2003;Ye et al, 2004;Tripathy and Roy, 2006), cervical cancers (Gao et al, 2011;Liu and Xu, 2012) and oral cancer ). However, a number of meta-analyses indicated no marked association of GSTM1 null mutations with hepatocellular cancer (White et al, 2008), brain tumours (Sima et al, 2012), colorectal cancers (Zhao et al, 2012), ovarian cancers (Economopoulos et al, 2010), melanoma (Nie et al, 2011). In this study, the results indicate that null GSTM1 genotype might increase susceptibility to NPC which was in accordance with the evidence-based meta-analysis pertaining to GSTM1 and GSTT1 polymorphisms on nasopharyngeal cancer by .…”
Section: Discussionsupporting
confidence: 88%
“…These include meta-analyses that suggest GSTM1 deficiency increases the risk of head and neck cancer (Hashibe et al, 2003;Ye et al, 2004;Tripathy and Roy, 2006), cervical cancers (Gao et al, 2011;Liu and Xu, 2012) and oral cancer ). However, a number of meta-analyses indicated no marked association of GSTM1 null mutations with hepatocellular cancer (White et al, 2008), brain tumours (Sima et al, 2012), colorectal cancers (Zhao et al, 2012), ovarian cancers (Economopoulos et al, 2010), melanoma (Nie et al, 2011). In this study, the results indicate that null GSTM1 genotype might increase susceptibility to NPC which was in accordance with the evidence-based meta-analysis pertaining to GSTM1 and GSTT1 polymorphisms on nasopharyngeal cancer by .…”
Section: Discussionsupporting
confidence: 88%
“…Further it was observed that GSTP1, GSTT1 and GSTM1 gene polymorphisms are not colorectal adenoma risk factors in a Chinese meta-analysis study conducted by Zhao et al [72] and Kassab et al [51] also showed that there is no significant risk with GSTM1 and GSTT1 null genotypes but a significant risk for CRC with GSTP1 in the Tunisian population.…”
Section: Gsts and Colorectal Cancermentioning
confidence: 95%
“…Several independent studies in diverse populations have all observed no significant associations of EPHX1 rs1051740 or rs2234922 SNPs with risk of colorectal carcinoma or adenoma development (Landi et al 2005, van der Logt et al 2006, Mitrou et al 2007, Hlavata et al 2010, Gilsing et al 2012, Zhao et al 2012). Nevertheless, a meta-analysis showed a trend towards a protective effect of SNP rs2234922 against colorectal cancer risk (Liu et al 2012).…”
Section: Ephx1 Role In Human Diseasementioning
confidence: 99%